LGBT tourism and cultural consumption, data, flows and resilience - Corbisiero, Fabio (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2019)
This issue begins with two papers on the homosexual community. Sociological works on Gays, Lesbians, Bisexuals and Transsexuals are increasingly numerous and widespread. People whose identities, claims and peculiarities are made up and recomposed in the LGBT acronym. The first two manuscripts of the journal offer female readers the answer to some of the sociological questions posed on the LGBT community in terms of cultural consumption, through unpublished field research data. The contribution by Roberta Bartoletti and Lorenzo Giannini inaugurates the thematic section with an empirical essay on LGBT tourism. The data of an exploratory survey on young homosexual Italian tourists are presented, aimed at collecting narratives of their travel experiences with a focus on the opportunities and limits of a market-mediated social inclusion of non-heterosexual gender identities. A picture of consumption practices is returned, implemented by homosexual people who intertwine social representations of homosexuality and stigma, self-directed behaviors and behavioral practices that connote certain differences in the travel and vacation styles of homosexual people compared to the behaviors of the mainstream population . [...]